Analisa Perubahan Geometri Penampang Sungai Menggunakan HEC-6 untuk Menaksir Debit Sedimen pada Sungai Citanduy di Jawa Barat - Wibowo, Hari (Department of Civil Engineering, Diponegoro University, 2013)
Formation of river profile is basically a process in the regulation of the water itself. This arrangement is based on the carrying capacity of the river flow is determined by the parameters of the flow and sediment transport. To assist in observing changes in the riverbed need a software that can predict changes in the cross-sectional shape of river bed. In this study HEC-6 to be able to estimate the fundamental changes Citanduy River in West Java by using field data parameters are available in the form of cross-sectional geometry of the river, flow rates, water levels are high by peil scale or board might guess from observation stations Citanduy Rive. River cross section data used in 2007 were used for the calibration data. Calibration process used for 2008. While the software application used to view changes in the existing cross-sectional shape. Discharge used in this case amounted to 27.717 m3/second and high cross-section downstream on Rajagosi area of 10.40 m. Model selection is done with a relatively small deviation. Obtained from the model calibration process that both sides Karang Pucung-Pataruman-Rajagosi the Manning roughness number